Evaluation of Catfish (Pangasius hypophthalmus) By-Products as protein sources for pigs in the Mekong Delta of Viet Nam - Nguyen, Thi Thuy (Dept. of Animal Nutrition and Management, Swedish University of Agricultural Sciences, 2010)
This book evaluates preservation methods of catfish by-products (CBP), and the effects of replacing marine fish meal (FM) with these processing by products on diet digestibility, performance, feed efficiency and carcass quality in growing-finishing pigs